ANALISA MARKETING MIX DALAM PENJUALAN MOTOR BEKAS PADA CV. PERSADA ARHTA SENTOSA BATAM - Nur Aye; Tibrani Tibrani; Dhenny Asmarazisa (EQUILIBIRIA, 2015)
The purpose of this study was to describe whether is a positive and significant influence between product,prince, promotion and place of the sale of used motorcycle on the CV. ArthaSentosaPersadaBatam.In this study, the authors use a sample of 100 consumers in the CV. ArthaSentosaPersadaBatam by questionnaire while the data used are primary data and secondary data. Sources of primary data and questionnaire results obtained from consumers on CV.  Artha Sentosa Persada Batam. Secondary data obtained from CV. ArthaSentosaPersadaBatam, related and can support as well as useful for this research. Data was collected by questionnaires, data were descriptive statistics, which are used to describe the function gives an overview of the object under study through the data sample or population that quantitative analysis of the data that has been given a score according to the scale liqueur and for test results using SPSS (Statistical Product Service Solution) version 20. From the research, the authors conclude products X1, Prince X2, promotions X3 and X4 locations and significant positive effect on sales of used motorcycles in the CV. ArthaSentosaPersadaBatam.